Hydrocarbon accumulation model influenced by “three elements (source-storage-preservation)” in lacustrine shale reservoir-A case study of Chang 7 shale in Yan’an area, Ordos Basin - Wang, Xiangzeng; Liang, Quansheng; Gao, Chao; Xue, Pei; Yin, Jintao; Hao, Shiyan (Frontiers in Earth Science, 2022)
The organic-rich shales of the Chang 7 Member in the Yan’an Formation of the Yan’an area, Ordos Basin is a hot spot for lacustrine shale gas exploration. In this paper, taking the Chang 7 Member shale in the Yan’an area as an example, the main controlling factors of lacustrine shale gas accumulation and the prediction of “sweet spots” are systematically carried out. The results show that the Yanchang Formation shale has the complete gas generating conditions. Shale gas accumulation requires three necessary accumulation elements, namely gas source, reservoir and good preservation conditions. The dynamic hydrocarbon generation process of the Chang 7 shale reservoirs is established according to the thermal simulation experiments of hydrocarbon generation, and the mechanism of catalytic degradation and gas generation in the Chang 7 Member under the background of low thermal evolution degree is revealed. The enriched authigenic pyrite can catalyze the hydrocarbon generation of organic matter with low activation energy, thereby increasing the hydrocarbon generation rates in the low-mature-mature stage. Different types of pores at different scales (2–100 nm) form a multi-scale complex pore network. Free gas and dissolved gas are enriched in laminar micro-scale pores, and adsorbed gas is enriched in nano-scale pores of thick shales, and silty laminates can improve the physical properties of the reservoir. This is because the laminar structure has better hydrocarbon generation conditions and is favorable for the migration of oil and gas molecules. The thickness of the lacustrine shale in the Chang 7 Member is between 40 and 120 m, which has exceeded the effective hydrocarbon expulsion thickness limit (8–12 m). At the end of the Early Cretaceous, the excess pressure of the Chang 7 shale was above 3 MPa. At present, horizontal wells with a daily gas production of more than 50,000 cubic meters are distributed in areas with high excess pressures during the maximum burial depth.